Yield and properties of bio-oil from the pyrolysis of mallee leaves in a fluidised-bed reactor - He, Min; Mourant, Daniel; Gunawan, Richard; Lievens, Caroline; Wang, Xiao; Ling, K.; Bartle, J.; Li, Chun-Zhu (Elsevier Science Ltd, 2012)
Mallee eucalypt crops from the low-rainfall dryland agricultural regions of southern Australia may become a major source of woody biomass for production of liquid biofuels through pyrolysis and biorefinery. Pyrolysis studies have commonly focused on the woody fraction and relatively little is known about the pyrolysis behaviour of leaves that make up a substantial portion of the overall plant biomass. In this study, mallee leaves were pyrolysed in a fluidized-bed reactor at temperatures ranging from 300 to 580 °C. The collected bio-oil products were characterised with various analytical techniques, including Karl Fischer titration, thermogravimetry, GC/MS, UV-fluorescence and FTIR spectroscopies. Our results show that, during pyrolysis, leaves behave very differently from the wood of the same mallee trees. Leaves tend to give a higher yield of char and a lower yield organics in bio-oil than the wood. The bio-oils produced from leaves and wood show distinctly different compositions. Eucalyptol, a chemical compound present in eucalyptus leaves, was found in high concentration in the bio-oils from the leaves.